Video discharge instructions for pediatric gastroenteritis in an emergency department: a randomized, controlled trial - Jové-Blanco, A. (Eur J Pediatr, 2020)
The aim was to evaluate if the addition of video discharge instructions (VDIs) to usual verbal information improved the comprehension of information provided to caregivers of patients who consult for acute gastroenteritis (AGE). We conducted an open-label, parallel, randomized trial, enrolling patients who consulted for AGE at a tertiary hospital. First, caregivers answered a written test concerning AGE characteristics and management. They were randomly allocated to a control group, which received the usual verbal instructions, or to an intervention group, which additionally received VDI. After discharge, caregivers were contacted by telephone and answered the same test, satisfaction questions, and follow-up information. From September 2019 to March 2020, 139 patients were randomized, 118 completed follow-up. The mean score was 3.13 (SD 1.07) over 5 points in the initial test and 3.96 (SD 0.96) in the follow-up test. Patients in the intervention group had a greater improvement (1.17 points, SD 1.11) than those in the control group (0.47 points, SD 0.94, p < 0.001). In the follow-up test, 49.1% in the intervention group and 18.6% in the control group answered all questions correctly (p < 0.001). There were no significant differences in return visits. Caregivers gave high satisfaction scores regardless of the allocation group. Conclusion: Video instructions improve caregivers’ understanding of discharge information. Trial registration: [NCT04463355, retrospectively registered July 9, 2020]. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00431-020-03827-w) contains supplementary material, which is available to authorized users.